Transvaginal natural orifice transluminal endoscopic surgery (VNOTES) total retroperitoneal sentinel lymph node biopsy for an endometrial cancer patient with prior colon cancer surgery - Comba, Cihan; Demirayak, Gökhan; Şimşek, Çiğdem; Şeker Ataş, Büşra; Özdemir, İsa Aykut (BMJ Publishing Group, 2021)
Endometrial cancer (EC) is the most common gynecological malignancy. Although EC is surgically staged, sentinel lymph node biopsy has become more widely used and has been featured in recently published guidelines for EC.
Keywords: Gynecologic Surgical Procedures; Endometrial Neoplasms; Laparoscopes; Sentinel Lymph Node